2010
DOI: 10.2139/ssrn.1631144
|View full text |Cite
|
Sign up to set email alerts
|

School Shootings and Student Performance

Abstract: Any opinions expressed here are those of the author(s) and not those of IZA. Research published in this series may include views on policy, but the institute itself takes no institutional policy positions.The Institute for the Study of Labor (IZA) in Bonn is a local and virtual international research center and a place of communication between science, politics and business. IZA is an independent nonprofit organization supported by Deutsche Post Foundation. The center is associated with the University of Bonn … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 22 publications
0
3
0
Order By: Relevance
“…This effect was not present for females. We do not have any specific explanation of this finding, but others have found a similar tendency in terms of worse exam results for boys after a school-shooting episode as compared with girls (Poutvaara & Ropponen, 2010). Likewise, boys seem to be more affected by maternal depression than girls, which may indicate different interacting genetic pathways influencing future health (Korhonen, Luoma, Salmelin, & Tamminen, 2012).…”
Section: Cognitive and Clinical Associationsmentioning
confidence: 60%
See 1 more Smart Citation
“…This effect was not present for females. We do not have any specific explanation of this finding, but others have found a similar tendency in terms of worse exam results for boys after a school-shooting episode as compared with girls (Poutvaara & Ropponen, 2010). Likewise, boys seem to be more affected by maternal depression than girls, which may indicate different interacting genetic pathways influencing future health (Korhonen, Luoma, Salmelin, & Tamminen, 2012).…”
Section: Cognitive and Clinical Associationsmentioning
confidence: 60%
“…One important finding from studies on school shootings is that in many survivors, their psychological and physiological suffering affected their everyday activities. Poutvaara and Ropponen (2010) analyzed the immediate effect of a school shooting in Finland in the middle of a national exam period. They found that the shooting decreased average test scores for boys but not for girls.…”
Section: Effects Of Terror Attacksmentioning
confidence: 99%
“…The few studies conducted in this area have mainly focused on academic performance and specific cognitive functions, and the results have been mixed (Chemtob et al., 2009; Melinder et al., 2015; Pfefferbaum et al., 2016; Scrimin et al., 2006; Syed et al., 2017). Studies on school or mass shootings add to this literature and consistently show impaired academic performance among survivors (Beland & Kim, 2016; Cabral et al., 2021; Gershenson & Tekin, 2018; Levine & McKnight, 2021; Poutvaara & Ropponen, 2010). Studies on school functioning following the Utøya terror event have in line with this research, demonstrated impaired academic performance among survivors (Bharadwaj et al., 2021; Schultz & Skarstein, 2021; Stene et al., 2019; Strøm et al., 2016).…”
mentioning
confidence: 99%